Spawning of the chilean hake (Merluccius gayi) in the upwelling system off Talcahuano in relation to oceanographic features - Cristian A. Vargas; Leonardo R. Castro (Scientia Marina, 2001)
Previous studies have shown that the upwelling area off Talcahuano, in central-south Chile, is an important spawning zone for the hake Merluccius gayi. We document the results of a study designed to assess the importance of oceanographic features on the horizontal and vertical distribution of hake eggs and larvae. Ichthyoplankton samples and oceanographic data (CTDO casts, and wind speed and direction) were collected during a cruise carried out off Talcahuano (36º22´S-37º10´S) in early spring (October 1996), which included a grid of 61 stations up to 60 nm offshore. The oceanographic information obtained revealed the presence of an upwelling plume at Lavapie Point (southern zone) extending northward over the shelf, and the presence of a warmer water parcel close to shore in the northern area. Peak egg densities occurred in this northern area over the shelf, in a nucleus located at the shoreward moving deeper layer (40-100 m deep) and associated with the upwelling front about 20-30 nm from shore. The highest larval abundance also occurred in the northern area over the shelf and in the deeper layer but closer to shore than the egg nucleus. Because the timing (early spring) and location of spawning (at depth, over the shelf and in association with frontal structures) are also shared by other hake species in upwelling areas, we propose that they may be part of a more commonly developed strategy to enhance offspring survival in coastal upwelling areas of eastern boundary currents.